The convergence of quantum science and the Islamic concept of the soul: exploring metaphysical realities - Norman, Nurul Ain; Al Walid, Kholid (Research Institute of Science and Strategic Evolution (RISSE), 2024)
In recent years, there has been a growing interest in the intersection between quantum science and spiritual or metaphysical concepts. This paper delves into the intriguing convergence between quantum science and the Islamic concept of the soul, aiming to explore the metaphysical realities that emerge from this intersection. Quantum science, with its revolutionary principles of superposition, entanglement, and non-locality, challenges our traditional understanding of reality, opening doors to new paradigms of thought. Similarly, the Islamic concept of the soul, deeply rooted in the Quranic worldview, posits the existence of a non-material essence that transcends the physical realm. By synthesising insights from both quantum science and Islamic theology, this paper seeks to illuminate the potential correlations and resonances between these seemingly disparate domains. Through a multidisciplinary approach, drawing from quantum mechanics and Islamic philosophy, this study aims to shed light on the nature of consciousness, the interconnectedness of all existence, and the ultimate reality of the human soul. By fostering dialogue and exploration at the nexus of science and spirituality, this research contributes to a deeper understanding of the fundamental mysteries of existence and the intricate relationship between the material and immaterial dimensions of reality.